ANALYSIS OF THE CHARACTERS OF INTERVIEW WITH THE VAMPIRE, A NOVEL BY ANNE - Diah Ikawati A. (Center of Language and Cultural Studies, 2016)
Analysis on the characters of novel Interview with the Vampire in this study presents characteristics of plot and the intrinsic elements of the novel. Results of analysis show the use of plot and characterization in this novel. Plot is the sequence of incidents or events of which a story is composed. The plot in this study covers exposition, conflict, complication, climax, and denouement. The plot is presented in raising form. The major characters as the characters that involved a great deal in a story are acted by Louis, Lestat, and Claudia. In addition, the minor characters involved in the story include Paul, Louis' sister, Babette, Lestat's father, Armand, Santiago, Madeleine, and the journalist. Theme and point of view in this novel are clearly stated, indicating that the novel has strong characterization.